Kualitas dan Kesuksesan Implementasi Sistem Informasi Kesehatan dengan Menggunakan Model Unified Theory of Acceptance and Use of Technology dan Model Delone and Mclean - Cindy Felita Nur Alimah Saptonoadi; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Homedika is a technology-based social entrepreneur that connects health workers and health facilities with various health services. Homedika established since November 2016 by dr. Gamal Albinsaid. This research has a purpose to know the quality and success implementation of Homedika. This research used model of Unified Theory Acceptance and Use of Technology (UTAUT) and DeLone & McLean model. The number of respondent that will be used for this research is 30 by using purposive sampling. Data were collected by questionnaire. The data analysis in this research used statistic descriptice. The results of quality analysis on the variable of social influence was high enough category. The results of success analysis on the variable of use was high enough category. The recommendation given in this research based on indicator that has a value below the total averages, there were subjective norm on social influence indicator and frequency of use indicator on use.